Investment in risky assets and participation in the financial market: does financial literacy matter? - Andreas Oehler; Matthias Horn; Stefan Wendt (International Review of Economics, 2023)
Our study contributes to a better understanding of the relationship between financial literacy and households' investments in risky assets. We estimate a structural equation model with data from the Panel on Household Finances of the German central bank. Our results show that although households' net wealth is the dominant driver of investments in risky assets, financial literacy plays a remarkable role. Financial literacy has an indirectly positive influence on participation in the financial market. The higher the financial literacy, the lower is the risk aversion. The lower the risk aversion, the higher is the participation in the financial market.
Keywords: D14; D81; D91; G11; G41; G51; 330; Financial markets participation; Risky investments; Personal finance; Household finance